Children's Rights In Public Spaces: Study Of Laman Boenda Park In Tanjungpinang City - Solina, Emmy; Rahmawati, Nanik; Igiasi, Teguh Sentiadika (LP2M INSURI Ponorogo, 2022)
This study aims to reveal some of the rights of children in public spaces by creating child-friendly public spaces after the description of children's rights in public spaces. Public space in urban areas has been transformed into a space for activities for urban communities such as the people of Tanjungpinang City. This study also reveals the variety of children's activities in the park, both with family and friends. This study also describes children's rights in their activities in public spaces by analyzing them with the eyes of a sociological study derived from various regulations regarding Child-Friendly Cities. This study uses a qualitative research method, where In obtained the informants through accidental sampling technique. The results of this study are expected to contribute ideas in dealing with urban problems in Tanjungpinang. They can also be an inspiration for families to be active in child-friendly public spaces. Penelitian ini bertujuan untuk mengungkap beberapa hak anak di ruang publik dengan menciptakan ruang publik yang ramah anak setelah penjabaran hak anak di ruang publik. Ruang publik di kawasan perkotaan telah menjelma menjadi ruang aktivitas bagi masyarakat perkotaan seperti masyarakat Kota Tanjungpinang. Studi ini juga mengungkap ragam aktivitas anak-anak di taman, baik bersama keluarga maupun teman. Kajian ini juga memaparkan hak-hak anak dalam beraktivitas di ruang publik dengan menganalisisnya dengan kacamata kajian sosiologis yang bersumber dari berbagai regulasi tentang Kota Layak Anak. Penelitian ini menggunakan metode penelitian kualitatif, dimana In memperoleh informan melalui teknik accidental sampling. Hasil penelitian ini diharapkan dapat memberikan sumbangsih pemikiran dalam menghadapi permasalahan perkotaan di Tanjungpinang. Mereka juga bisa menjadi inspirasi bagi keluarga untuk aktif di ruang publik ramah anak.